Solar photovoltaic panel soiling accumulation and removal methods: A review - Yunpeng Liu; Haoyi Li; Le Li; Xiaoxuan Yin; Xinyue Wu; Zheng Su; Fengsheng Gao; BinBin Cai; Li Tang; Songsong Zhou (IET Renewable Power Generation)
Abstract Photovoltaic (PV) power generation has become a key area for investment worldwide. Solar PV panels are the core components of PV power generation systems, and the accumulation of soiling on their surfaces has numerous adverse effects on power generation. This paper provides an overview of the soiling accumulation on PV panels and the existing soiling removal methods. Firstly, the sources of soiling particles and the mechanism of soiling fall are analyzed, based on which the accumulation of soiling on the surface of the PV panels is described in detail, and then the effect of the surface soiling on the PV panels is investigated in the order of optics‐thermology‐electrical, with the necessary semiempirical formulas provided to assist in more in‐depth analyses. In addition, the principles, status quo, effects, costs, advantages, and disadvantages of existing soiling removal methods are specifically described, thus providing a reference for the selection of soiling removal methods in different regions. The paper also analyses the soiling accumulation and removal challenges of PV panels in different regions of China. The results of the study are important for the improvement of the effectiveness of soiling removal and the rational optimization of the soiling removal scheme.